1990
DOI: 10.1016/0309-1651(90)90068-a
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in collagen metabolism and response to hypertonic culture conditions of rat aortic smooth muscle cells and skin fibroblasts

Abstract: The rates of growth and collagen synthesis of rat aortic smooth muscle cells in culture were decreased with increasing the age of the animals from which the cells were obtained. These rates were further decreased by the presence of a 0.1 M excess concentration of KCl in the culture medium, and the cells obtained from older animals were much more sensitive to the inhibitory effect of the hypertonic culture condition. These tendencies were observed in smooth muscle cells obtained from different phases of in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because vessel wall synthesis occurs early in development, [25][26][27] collagen expression in neonatal animals was assessed. RNA was isolated from pooled aortas of neonatal (6 days old) WT and line 16 mice, and Northern blot analysis was performed ( Figure 1E).…”
Section: Neonatal Transgenic and Wt Mice Display Elevated Levels Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Because vessel wall synthesis occurs early in development, [25][26][27] collagen expression in neonatal animals was assessed. RNA was isolated from pooled aortas of neonatal (6 days old) WT and line 16 mice, and Northern blot analysis was performed ( Figure 1E).…”
Section: Neonatal Transgenic and Wt Mice Display Elevated Levels Of Cmentioning
confidence: 99%
“…Thus, cyclin A alleviates B-myb-mediated repression of the ␣1(I) collagen promoter, similar to its effects on the ␣2(V) promoter. 20 Because the bulk of matrix synthesis occurs early during development, [25][26][27] the presence of cyclin A likely explains, at least in part, why no significant differences were observed in collagen deposition in the vessel wall of transgenic animals.…”
Section: Neonatal Transgenic and Wt Mice Display Elevated Levels Of Cmentioning
confidence: 99%
“…Variations in the relative rates of synthesis of extracellular matrix components were demonstrated in physiological as well as pathological conditions such as aging, UV radiations, a variety of skin diseases. Although total collagen synthesis decreases slowly with age [17,18], the relative proportion of collagen III was shown to increase with age and also in pathologies such as diabetes [19]. It could be shown that the biosynthesis of fibronectin increases with chronological age [20] and in vitro as a function of passage number of fibroblasts [16].…”
Section: Introductionmentioning
confidence: 99%